Safe sites for buccal shelf bone screw placement in various skeletal malocclusions: A CBCT study - V M Athira; Keerthan Shashidhar; M N Kuttappa; U S Krishna Nayak; M S Ravi; Neevan D' Souza (Wolters Kluwer Medknow Publications, 2023)
INTRODUCTION: The mandibular buccal shelf area is an extra-alveolar anchorage site that has high quality and quantity of bone, provides biomechanical benefits and has low failure rates. It is essential to place the implant in the region of bone with optimal thickness. The aim of this study was to determine the suitable site of the mandibular buccal shelf for bone screw insertion at 90 degrees and 30 degrees angles of insertion and various heights, angulations, areas of the buccal shelf in prognathic and retrognathic mandibles, and vertical and horizontal growth patterns. METHODS: In this retrospective study, we evaluated the cone-beam computed tomography (CBCT) images of 48 patients in the age range of 18-30 years, divided into four groups. Seven sectional sites were examined at 3, 5, and 7 mm from the alveolar crest at 90 degrees and 30 degrees. The angulation and area of the buccal shelf were examined. RESULTS: Cortical bone thickness increased distally from the first to the second molar in all four groups. CONCLUSIONS: The preferred site for buccal shelf implant placement was distal to the mandibular second molar. The maximum amount of cortical bone was observed distal to the second molar, 7 mm vertically from the alveolar crest, when the buccal shelf implant was placed at 30 degrees angulation to the long axis of the tooth.